The sum of three numbers in A.P. is 12, and the sum of their cubes is 408; find them.
Answer
Verified
509.4k+ views
Hint: Assume the numbers as (a – d), a, (a + d) and apply the conditions to solve to get the values of ‘a’ and ‘d’ and after that put that values in assumed numbers to get the answer.
Complete step-by-step answer:
As we have given that the three numbers are in A.P. and therefore we will assume (a-d), a, (a+d) as the three numbers in A.P. with ‘a’ as the first term and‘d’ is the common difference.
As the sum of three numbers is 12, therefore we can write,
(a - d) + a + (a + d) = 12
$\Rightarrow $a - d + a + a + d = 12
$\Rightarrow $a + a + a = 12
$\Rightarrow $ 3a = 12
$\Rightarrow a=\dfrac{12}{3}$
$\Rightarrow $ a = 4 …………………………………. (2)
Now, as per the second condition given in the problem we can write,
$\therefore {{\left( a-d \right)}^{3}}+{{a}^{3}}+{{\left( a+d \right)}^{3}}=408$
If we put the value equation (2) in the middle term of the above equation we will get,
$\Rightarrow {{\left( a-d \right)}^{3}}+{{4}^{3}}+{{\left( a+d \right)}^{3}}=408$
$\Rightarrow {{\left( a-d \right)}^{3}}+64+{{\left( a+d \right)}^{3}}=408$
$\Rightarrow {{\left( a-d \right)}^{3}}+{{\left( a+d \right)}^{3}}=408-64$
$\Rightarrow {{\left( a-d \right)}^{3}}+{{\left( a+d \right)}^{3}}=344$ ………………………………… (3)
Now to proceed further in the solution we should know the formula given below,
Formula:
\[\left( {{x}^{3}}+{{y}^{3}} \right)=\left( x+y \right)\times \left( {{x}^{2}}+{{y}^{2}}-xy \right)\]
By using above formula we can write equation (3) as follows,
\[\therefore \left[ \left( a-d \right)+\left( a+d \right) \right]\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( a-d \right)\times \left( a+d \right) \right]=344\]
\[\therefore \left[ a-d+a+d \right]\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( a-d \right)\times \left( a+d \right) \right]=344\]
\[\therefore \left[ a+a \right]\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( {{a}^{2}}+ad-ad-{{d}^{2}} \right) \right]=344\]
\[\therefore 2a\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( {{a}^{2}}-{{d}^{2}} \right) \right]=344\]
\[\therefore 2a\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-{{a}^{2}}+{{d}^{2}} \right]=344\]
Now to proceed further we should know the formulae given below,
Formulae:
\[{{\left( x+y \right)}^{2}}=\left( {{x}^{2}}+2xy+{{y}^{2}} \right)\] And \[{{\left( x+y \right)}^{2}}=\left( {{x}^{2}}-2xy+{{y}^{2}} \right)\]
By using the above formulae we can write the above equation as,
\[\therefore 2a\times \left[ \left( {{a}^{2}}-2ad+{{d}^{2}} \right)+\left( {{a}^{2}}+2ad+{{d}^{2}} \right)-{{a}^{2}}+{{d}^{2}} \right]=344\]
By opening the brackets we will get,
\[\Rightarrow 2a\times \left[ {{a}^{2}}-2ad+{{d}^{2}}+{{a}^{2}}+2ad+{{d}^{2}}-{{a}^{2}}+{{d}^{2}} \right]=344\]
\[\Rightarrow 2a\times \left[ {{d}^{2}}+{{a}^{2}}+{{d}^{2}}+{{d}^{2}} \right]=344\]
\[\Rightarrow 2a\times \left[ 3{{d}^{2}}+{{a}^{2}} \right]=344\]
By substituting the value of equation (2) in the above equation we will get,
\[\Rightarrow 2\times 4\times \left[ 3{{d}^{2}}+{{4}^{2}} \right]=344\]
\[\Rightarrow 8\times \left[ 3{{d}^{2}}+{{4}^{2}} \right]=344\]
\[{{\left( x+y \right)}^{3}}and{{\left( x-y \right)}^{3}}\]
\[\Rightarrow 3{{d}^{2}}+16=43\]
\[\Rightarrow 3{{d}^{2}}=43-16\]
\[\Rightarrow 3{{d}^{2}}=27\]
\[\Rightarrow {{d}^{2}}=\dfrac{27}{3}\]
\[\Rightarrow {{d}^{2}}=9\]
By taking square roots on both sides of the equation we will get,
\[\therefore d=\pm 3\]
Therefore d = 3 OR d = -3 ……………………………………. (4)
Now we will rewrite the three numbers below,
(a – d), a, (a + d)
If we put the values of equation (2) and equation (4) in above equation as shown below,
a = 4 and d = 3
Therefore numbers will become,
(4 – 3), 4, (4+3)
Therefore the numbers are,
1, 4, 7.
Now,
a = 4 and d = - 3
Therefore numbers will become,
[4 – (-3)], 4, [4+(-3)]
(4 + 3), 4, (4 – 3)
Therefore the numbers are,
7, 4, 1.
Therefore the three numbers are 1, 4, 7 or 7, 4, 1.
Note: Assume the standard numbers given by (a – d), a, (a + d) to make the calculations easier. Also in the step ${{\left( a-d \right)}^{3}}+{{\left( a+d \right)}^{3}}=344$ you can also use the formulae of \[{{\left( x+y \right)}^{3}}and{{\left( x-y \right)}^{3}}\]
Complete step-by-step answer:
As we have given that the three numbers are in A.P. and therefore we will assume (a-d), a, (a+d) as the three numbers in A.P. with ‘a’ as the first term and‘d’ is the common difference.
As the sum of three numbers is 12, therefore we can write,
(a - d) + a + (a + d) = 12
$\Rightarrow $a - d + a + a + d = 12
$\Rightarrow $a + a + a = 12
$\Rightarrow $ 3a = 12
$\Rightarrow a=\dfrac{12}{3}$
$\Rightarrow $ a = 4 …………………………………. (2)
Now, as per the second condition given in the problem we can write,
$\therefore {{\left( a-d \right)}^{3}}+{{a}^{3}}+{{\left( a+d \right)}^{3}}=408$
If we put the value equation (2) in the middle term of the above equation we will get,
$\Rightarrow {{\left( a-d \right)}^{3}}+{{4}^{3}}+{{\left( a+d \right)}^{3}}=408$
$\Rightarrow {{\left( a-d \right)}^{3}}+64+{{\left( a+d \right)}^{3}}=408$
$\Rightarrow {{\left( a-d \right)}^{3}}+{{\left( a+d \right)}^{3}}=408-64$
$\Rightarrow {{\left( a-d \right)}^{3}}+{{\left( a+d \right)}^{3}}=344$ ………………………………… (3)
Now to proceed further in the solution we should know the formula given below,
Formula:
\[\left( {{x}^{3}}+{{y}^{3}} \right)=\left( x+y \right)\times \left( {{x}^{2}}+{{y}^{2}}-xy \right)\]
By using above formula we can write equation (3) as follows,
\[\therefore \left[ \left( a-d \right)+\left( a+d \right) \right]\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( a-d \right)\times \left( a+d \right) \right]=344\]
\[\therefore \left[ a-d+a+d \right]\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( a-d \right)\times \left( a+d \right) \right]=344\]
\[\therefore \left[ a+a \right]\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( {{a}^{2}}+ad-ad-{{d}^{2}} \right) \right]=344\]
\[\therefore 2a\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-\left( {{a}^{2}}-{{d}^{2}} \right) \right]=344\]
\[\therefore 2a\times \left[ {{\left( a-d \right)}^{2}}+{{\left( a+d \right)}^{2}}-{{a}^{2}}+{{d}^{2}} \right]=344\]
Now to proceed further we should know the formulae given below,
Formulae:
\[{{\left( x+y \right)}^{2}}=\left( {{x}^{2}}+2xy+{{y}^{2}} \right)\] And \[{{\left( x+y \right)}^{2}}=\left( {{x}^{2}}-2xy+{{y}^{2}} \right)\]
By using the above formulae we can write the above equation as,
\[\therefore 2a\times \left[ \left( {{a}^{2}}-2ad+{{d}^{2}} \right)+\left( {{a}^{2}}+2ad+{{d}^{2}} \right)-{{a}^{2}}+{{d}^{2}} \right]=344\]
By opening the brackets we will get,
\[\Rightarrow 2a\times \left[ {{a}^{2}}-2ad+{{d}^{2}}+{{a}^{2}}+2ad+{{d}^{2}}-{{a}^{2}}+{{d}^{2}} \right]=344\]
\[\Rightarrow 2a\times \left[ {{d}^{2}}+{{a}^{2}}+{{d}^{2}}+{{d}^{2}} \right]=344\]
\[\Rightarrow 2a\times \left[ 3{{d}^{2}}+{{a}^{2}} \right]=344\]
By substituting the value of equation (2) in the above equation we will get,
\[\Rightarrow 2\times 4\times \left[ 3{{d}^{2}}+{{4}^{2}} \right]=344\]
\[\Rightarrow 8\times \left[ 3{{d}^{2}}+{{4}^{2}} \right]=344\]
\[{{\left( x+y \right)}^{3}}and{{\left( x-y \right)}^{3}}\]
\[\Rightarrow 3{{d}^{2}}+16=43\]
\[\Rightarrow 3{{d}^{2}}=43-16\]
\[\Rightarrow 3{{d}^{2}}=27\]
\[\Rightarrow {{d}^{2}}=\dfrac{27}{3}\]
\[\Rightarrow {{d}^{2}}=9\]
By taking square roots on both sides of the equation we will get,
\[\therefore d=\pm 3\]
Therefore d = 3 OR d = -3 ……………………………………. (4)
Now we will rewrite the three numbers below,
(a – d), a, (a + d)
If we put the values of equation (2) and equation (4) in above equation as shown below,
a = 4 and d = 3
Therefore numbers will become,
(4 – 3), 4, (4+3)
Therefore the numbers are,
1, 4, 7.
Now,
a = 4 and d = - 3
Therefore numbers will become,
[4 – (-3)], 4, [4+(-3)]
(4 + 3), 4, (4 – 3)
Therefore the numbers are,
7, 4, 1.
Therefore the three numbers are 1, 4, 7 or 7, 4, 1.
Note: Assume the standard numbers given by (a – d), a, (a + d) to make the calculations easier. Also in the step ${{\left( a-d \right)}^{3}}+{{\left( a+d \right)}^{3}}=344$ you can also use the formulae of \[{{\left( x+y \right)}^{3}}and{{\left( x-y \right)}^{3}}\]
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE